The refugee and asylum seeker mental health treatment screener (RAS-MT-screener): feasibility and psychometric properties of a questionnaire detecting refugees' and asylum seekers' need and urgency for mental health treatment - Nagy, Ede; Herpertz, Sabine; Schohl, Katharina; Zehetmair, Catharina; Gebhardt, Nadja; Friederich, Hans-Christoph; Nikendei, Christoph (General hospital psychiatry, 2023)
Objective - Refugees and asylum seekers are highly vulnerable to the development of mental health problems, yet oftentimes their need is underestimated. We aimed to develop a culturally sensitive screening tool for primary care settings assessing the urgency and need for mental health treatment to close this gap. - Method - Items for the screening tool were selected out of an item pool generated by a group of clinical experts based on the data obtained from n = 307 asylum seekers in a refugee state registration and reception center in Germany. Out of these, n = 111 attended a psychosocial walk-in clinic, and clinicians' ratings of urgency and need for mental health treatment were added. - Results - The resulting questionnaire comprised 8 items assessing urgency and 13 items assessing need for mental health treatment. Sensitivity was =0.74 and specificity =0.70. Participants of clinical and non-clinical samples differ highly significantly (p < .001). Cross-cultural validity was shown by comparing measurement invariance for different countries of origin. - Conclusion - The RAS-MT-Screener is a clinically and cross-culturally valid screening tool in primary care settings for the urgency and need for mental health treatment with acceptable psychometric properties. Future research on its external and construct validity is warranted.
Online verfügbar 25. März 2023, Artikelversion 24. April 2023
Gesehen am 16.06.2023